HUBUNGAN PERSEPSI DAN PERILAKU IBU TERHADAP IMUNISASI TAMBAHAN PADA BAYI (USIA 2 BULAN-12 BULAN) DENGAN KEJADIAN PNEUMONIA - Astuti, Indah Puji; Damayanti, Fitriani Nur; Mustika, Dian Nintyasari (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
One of morbidity in children under five and can cause death was pneumonia. Pneumonia is a disease that can be prevented by giving the Hib / Pneumococus. Data UNICEF child mortality in Indonesia show in 2012 is 14%, or about 21 thousand children die from pneumonia. Data results Demography and Population Survey Indonesia in 2012 Pneumonia is referred to as the number one killer of children under five years. The purpose of this study was to determine the relationship of maternal perception and behavior towards additional immunization in infants (age 2-12 months) with the occurrence of pneumonia at children in Puskesmas Candilama Semarang. Survey cross sectional analytic approach. Research subjects 70 respondents, taken by means of random sampling system. The independent variable is the perception and behavior of the mother while the dependent variable is an additional immunization in infants (age 2-12 months). Appliance using a questionnaire.Â  There was a relationship between perception and behavior signifikant mother against additional immunization in infants (age 2-12 months) with the occurrence ofÂ  pneumonia at children in Puskesmas Candilama Semarang. P value 18.806. The results of correlation with the chi square test showed there is relationship between perception and behavior signifikant mother towards additional immunization in infants (age 2-12 months) with the occurence of pneumonia at children in Puskesmas Candilama Semarang. Keywords : Perception, Behavior, Additional Immunization In Infant (Age 2-12 Months), Pneumonia